Lectin-binding characteristics of a Lyme borreliosis spirochete Borrelia burgdorferi sensu stricto - Vancová, M; Nebesárová, J; Grubhoffer, L (Folia microbiologica, 2005)
Borrelial glycoconjugates were localized by labeled lectins on ultrathin cryosections and on surfaces of intact negatively stained bacteria. Protein-saccharide complexes in these glycoconjugates were partially characterized by means of enzyme deglycosylation and mild alkali pretreatment of cryosections. The results of labeling were examined by transmission electron microscopy. Statistically evaluated results (relative labeling index, chi2 test) of gold labeling indicated that surfaces of Borrelia burgdorferi strain B31 and external (outer) membrane vesicles (MVs) were covered with glycoconjugates containing O-glycosidically linked N-acetyl-D-galactosamine (GalNAc) and N-glycosidically linked N-acetyl-D-glucosamine (GlcNAc). The presence of N-linked GalNAc, sialic acid, mannose and fucose on the surfaces of outer membranes and MVs was probably due to an adherence of BSK-H medium components, especially rabbit serum, to Borrelia surfaces.
Keywords: lektiny; Borrelia burgdorferi; lymeská nemoc; Cryoelectron Microscopy; Lyme Disease; glykokonjugáty; techniky in vitro; Glycoconjugates; králíci; Cell Membrane; Animals; lidé; elektronová kryomikroskopie; Lectins; Humans; zvířata; buněčná membrána; Rabbits; In Vitro Techniques